From sarcopenia to frailty: a road less traveled. Issue 1 (14th February 2014) - Morley, John E.; von Haehling, Stephan; Anker, Stefan D.; Vellas, Bruno
Abstract : The physical frailty phenotype consists of fatigue, weight loss, and loss of muscle power. Sarcopenia has been shown to be a major cause of frailty. Six societies including SCWD published a consensus suggesting that all persons older than 70 years of age should be screened for frailty when seeing health professionals. Simple screening tests such as the FRAIL (fatigue, resistance, aerobic, illness, and loss of weight) scale can be used. It is felt that frailty can be treated by exercise (resistance and aerobic), high quality protein, vitamin D, and treatment of the common causes of fatigue. It is expected that this approach will decrease disability in older persons.